Holbein capturing character - Woollett, Anne T.; Mackelaitè, Austėja; McQuillen, John T.; Birkmaier, Ulrich Hans; Hand, John Oliver 1941- (J. Paul Getty Museum, 2021)
"This publication was prepared to accompany the exhibition Holbein: Capturing Character, scheduled to open at the J. Paul Getty Museum at the Getty Center, Los Angeles, in 2021, and at the Morgan Library & Museum, New York, in 2022. The catalogue explores Hans Holbein's approach to portraiture and self-identity in the Renaissance"--
Impressum: This publication is issued on the occasion of the exhibition 'Holbein: Capturing Character', on view at the J. Paul Getty Museum at the Getty Center, Los Angeles, from October 19, 2021, to January 9, 2022, and the Morgan Library & Museum, New York, from February 11 to May 15, 2022
Keywords: Holbein, Hans -- 1497-1543; Bildnismalerei; Holbein, Hans / 1497-1543 / Exhibitions; Holbein, Hans / 1497-1543 / Criticism and interpretation; Portrait painting, German / 16th century / Exhibitions; Portrait drawing, German / 16th century / Exhibitions; Portraits, Renaissance / Exhibitions; Art, Renaissance / Exhibitions; Holbein, Hans / 1497-1543; Art, Renaissance; Portrait drawing, German; Portrait painting, German; Portraits, Renaissance; 1500-1599; Criticism, interpretation, etc; Exhibition catalogs; Ausstellungskatalog -- J. Paul Getty Museum -- 19.10.2021-09.01.2022 -- Los Angeles, Calif.; Ausstellungskatalog -- The Morgan Library & Museum -- 11.02.2022-15.05.2022 -- New York, NY